Discrepancies between farmers' perceptions and actual animal welfare conditions on commercial pig farms - Nadlučnik, Eva; Golinar Oven, Irena; Tomažič, Iztok; Plut, Jan; Dovč, Alenka; Štukelj, Marina (Frontiers in Veterinary Science, 2022)
Animal welfare is a multiparameteral concept that encompasses the physical and mental health of animals and includes various aspects such as physical well-being, absence of hunger and thirst, and ability to express motivated behavior, to which farmers usually attach different importance. The objectives of this study were to evaluate animal welfare on Slovenian commercial pig farms, to determine whether farmers' perceived importance of animal welfare differ from actual animal welfare on farms and to determine, if farmer’s age, gender, their level of education and participation in vocational training have an influence. For that purpose, we created an Animal Welfare Protocol/Questionnaire for Pig Farms (AWQ/P-P) that assessed several parameters of animal welfare: (1) general status, (2) animal behavior, (3) health status, (4) living conditions, and (5) environmental conditions. Each parameter included at least five observation points and was scored on a 5-point scale. The same observation points were used to measure farmers' perceived importance of animal welfare and for observational assessment. Consequently, we were able to compare both statistically. Farmers from fourteen (N = 14) large Slovenian pig farms participated in the study. Results show that farmers rate all parameters of animal welfare very highly. For them, animal health status is the most important, and environmental conditions are the least important factors for animal welfare. Observational inspections yielded significantly lower scores for animal welfare conditions than those obtained from farmer ratings. The highest correlations between farmers' perceptions and observational inspections were found for the parameters of animal behavior and environmental conditions. The results of this study also suggest that vocational training is a significant variable in increasing levels of pig welfare. Age, gender, and education level are not significant variables, however, farms led by older male farmers with lower level of education but involved in vocational training from different sources had slightly better welfare on the farm. This should be further investigated before making conclusions, due to our small sample size. The significance of the study is to identify deficiencies in pig welfare as perceived by farmers and consequently improve pig welfare.